Sarcopenia and Physical Activity Predict Falls in Older Adults from Amazonas, Brazil (La sarcopenia y la actividad física predicen caídas en adultos mayores de Amazonas, Brasil) - Kessketlen Alves Miranda; Élvio Rubio Gouveia; Bruna Gouveia; Adilson Marques; Pedro Campos; Antonieta Tinôco; Jefferson Jurema; Matthias Kliegel; Andreas Ihle (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Sarcopenia is a progressive and widespread skeletal muscle disorder involving loss of muscle mass and function, and is associated with several outcomes, including falls, functional decline, frailty, and mortality. Therefore, this study aimed: (1) to estimate the prevalence of sarcopenia, falls, and the risk of falls considering age, sex, and the level of physical activity (PA), and (2) to identify which of these predictors better explained the likelihood that participants present risk of fall. A total of 701 participants (433 women) with a mean age of 70.4±6.9. Sarcopenia was determined according to the most recent guidelines from the European Working Group (EWGSOP2). The prevalence of falls and the level of physical activity were assessed by questionnaires. The risk of falls was assessed using the Fullerton Advance Balance (FAB) scale. This study provides evidence that women (OR: 2.5, p<0.001), the oldest people (OR: 1.1 p<0.001), and people who had identified sarcopenia (OR: 2.9 p<0.001), and lower level of physical activity (OR: 2.9 p<0.001), were more likely to present the risk of falls. Implications for vulnerable aging are discussed.